Optimal Dispatch of a Virtual Storage Plant Using Inexact ADMM - Cai, Defu; Wang, Zuowei; Wang, Xiao; Wang, Yang; Wang, Wenna; Zhou, Kunpeng; Yu, Dehua (Frontiers in Energy Research, 2022)
A virtual storage plant (VSP) is identified as an effective approach to aggregating distributed storage devices participating in power network supports with similar capability as bulk storage systems. In this study, we develop a distributed control framework for cost-effective storage coordination in the distribution networks, in which the energy storage units are coordinated to contribute to a given power reference at the aggregated level while regulating the local network voltages in the presence of renewable generations. The salient features of the proposed VSP control roots from the successful employment of an inexact alternating direction method of multiplier (ADMM) algorithm, in which the primal updates have analytical solutions in closed form using proximal operators, which significantly reduces the computation efforts of individual storage agents, and renders fast storage dispatch. The proposed control is favorable for near real-time storage dispatch in an optimal manner, and its effectiveness is demonstrated using realistic distributed networks in the simulations.